On the permanent component profiling of the negative bias temperature instability in p-MOSFET devices. (April 2015) - Djezzar, Boualem; Tahi, Hakim; Benabdelmoumene, Abdelmadjid; Chenouf, Amel; Goudjil, Mohamed; Kribes, Youcef
Highlights: Depth profiling of NBTI permanent component. Effective dipole moment ( aeff ) and activation energy ( Ea ) are linearly related to depth ( Z ). Fast and slow border traps of the interfacial sub-oxide layer in NBTI degradation. Permanent component is related to the Pb center hydrogen complex located in the interfacial sub-oxide region. NBTI progression from interface to border oxide region. Abstract: In this manuscript, we have investigated the negative bias temperature instability (NBTI) induced border-trap ( Nbt ) depth in the interfacial oxide region of PMOS transistors using multi-frequency charge pumping (MFCP) method. We emphasize on the distribution of the permanent component in the oxide near the interface, giving a clear insight on its effect on NBTI features. According to the experimental data, the extracted effective dipole moment ( aeff ) and field-independent activation energy ( Ea ) have revealed a linear relation with depth distance ( Z ), which consistently explain the variation of n as well as Ea, eff often reported in the literature. In fact, aeff and Ea increase with the depth, indicating the presence of the precursor defects having different effective dipole moments and activation energies. We suggest that such traps are most likely related to O3 − x Si x Si–H ( x = 1 and x = 2) family defects (or Pb center hydrogen complex) located in the interfacial sub-oxide region.